2013
DOI: 10.1371/journal.pone.0082314
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Image Studies on Tumor Nests Mathematical Features of Breast Cancer and Their Clinical Prognostic Value

Abstract: BackgroundThe expending and invasive features of tumor nests could reflect the malignant biological behaviors of breast invasive ductal carcinoma. Useful information on cancer invasiveness hidden within tumor nests could be extracted and analyzed by computer image processing and big data analysis.MethodsTissue microarrays from invasive ductal carcinoma (n = 202) were first stained with cytokeratin by immunohistochemical method to clearly demarcate the tumor nests. Then an expert-aided computer analysis system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 38 publications
1
30
0
1
Order By: Relevance
“…So, rich information on tumor recurrence and metastasis hidden in the primary tumor should be explored in future study to supply prognostic information which could not be revealed by the current TNM staging system. Our previous study indicated predictive performance of breast cancer information in situ on prognosis was higher than N stage (Wang et al, 2013). Therefore, with the changing clinical scenario, new staging systems other than TNM staging should be developed to better subdivide early stage BC patients for more appropriate personalized therapies.…”
Section: Discussionmentioning
confidence: 99%
“…So, rich information on tumor recurrence and metastasis hidden in the primary tumor should be explored in future study to supply prognostic information which could not be revealed by the current TNM staging system. Our previous study indicated predictive performance of breast cancer information in situ on prognosis was higher than N stage (Wang et al, 2013). Therefore, with the changing clinical scenario, new staging systems other than TNM staging should be developed to better subdivide early stage BC patients for more appropriate personalized therapies.…”
Section: Discussionmentioning
confidence: 99%
“…These computational approaches can be complementary with other clinical evaluation methods to improve pathologists' knowledge of the disease and improve treatments [21,4]. For example, previous studies have shown more accurate diagnosis results are derived by integrating information extracted from computational pathology with patients' clinical data for various cancer types such as prostate cancer [6,17], lung cancer [28], breast cancer [83,16], colorectal cancer [42], and ovarian cancer [36]. In particular, computerized image processing technology has been shown to improve performance, correctness, and robustness in histopathology assessments [47].…”
Section: Introductionmentioning
confidence: 99%
“…Although surgery, radiotherapy, chemotherapy and endocrine therapy are widely applied in clinics, long-term survival rates have not significantly improved (3). Each year ~500,000 individuals succumb to the disease; the leading cause of breast cancer-associated mortality is tumor metastasis, which remains a challenge for the prophylaxis and treatment of breast cancer (4).…”
Section: Introductionmentioning
confidence: 99%